1999
DOI: 10.1055/s-0037-1614629
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombogenic Coating of Stents Using a Biodegradable Drug Delivery Technology

Abstract: SummaryTo reduce the thrombogenic properties of coronary artery stents, a biodegradable polylactic acid (PLA) stent coating with an incorporated thrombin inhibitor and a platelet aggregation inhibitor has been developed. In an ex vivo human stasis model, its effect on platelets, plasmatic coagulation and its release characteristics were studied using whole blood. Bare steel and bare gold-surface stents were compared to steel and gold-surface stents coated with PLA (30 kDa) containing 5% polyethyleneglycol (PEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 29 publications
0
51
0
3
Order By: Relevance
“…20,21 Thrombotic occlusion of either polymercovered or polymeric stents has also been reported earlier in experimental models. 7,22,23 On the other hand, a number of studies have demonstrated that immobilized heparin and hirudin are able to improve the haemocompatibility of both SS and polymeric surfaces, [12][13][14]24 although the potential risk for heparininduced thrombocytopenia (HIT) and subsequent platelet activation are of continuing concern. Furthermore, heparin is known to have a dual role in blood coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Thrombotic occlusion of either polymercovered or polymeric stents has also been reported earlier in experimental models. 7,22,23 On the other hand, a number of studies have demonstrated that immobilized heparin and hirudin are able to improve the haemocompatibility of both SS and polymeric surfaces, [12][13][14]24 although the potential risk for heparininduced thrombocytopenia (HIT) and subsequent platelet activation are of continuing concern. Furthermore, heparin is known to have a dual role in blood coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Als Alternative stehen biodegradierbare Trägersysteme wie Polylaktide und Polyglykolide zur Verfügung [9,10,33,47,48]. Kürzlich wurde eine kalte Beschichtungstechnologie entwickelt, die es erlaubt, Implantate mit Trägermaterial zu überziehen [16,50]. In diese biodegradierbare Poly-(D,L-laktid) (PDLLA)-Beschichtung können biologisch aktive Substanzen (z.…”
Section: Schlüsselworteunclassified
“…Die Beschichtungstechnologie und die Eigenschaften der PDLLA-Beschichtung wurden bereits ausführlich beschrieben [16,50]. In Gruppe 3 und 4 wurden 150 µg rekombinantes humanes "bone morphogenetic protein-2" (rhBMP-2, Theodor-Boveri-Institut, Würzburg, Deutschland) in die PDLLA-Beschichtung integriert bzw.…”
Section: Beschichtung Der Cagesunclassified
See 1 more Smart Citation
“…4,25 In coronary stents, antithrombotic drugs were incorporated into a biodegradable PDLLA coating and led to significant reduction of local thrombotic reactions and restenoses of coronary vessels. 5,26 Gombotz et al described the controlled release of biologically active TGF-␤1 from a biodegradable poly(D,L-lactic-co-glycolic acid) and demineralized bone matrix. 27 The local application of recombinant human bone morphogenetic protein (rh-BMP-2) from collagen sponges or bio-absorbable poly(D,Llactide-coglycolide) (PLA/PGA) beads with osteopromotive membranes into rat mandibular defects shows a superior bone regeneration using PLA/PGA than a collagen carrier.…”
Section: Introductionmentioning
confidence: 99%